Preservation and enumeration of endothelial progenitor and endothelial cells from peripheral blood for clinical trials. (July 2015) - Bogoslovsky, Tanya; Maric, Dragan; Gong, Yunhua; Qu, Baoxi; Yang, Kelly; Spatz, Maria; Hallenbeck, John; Diaz-Arrastia, Ramon
Aims: Endothelial progenitor cells (EPCs) are markers of vascular repair. Increased numbers of circulating endothelial cells (ECs) are associated with endothelial damage.Materials & Methods: We enumerated EPC-EC by using Enrichment kit with addition of anti-human CD146-PE/Cy7 from peripheral blood mononuclear cell (PBMC) isolated either by red blood cell (RBC) lysing solution or by Ficoll centrifugation, and from fresh and preserved samples. PBMCs were quantified by flow cytometry.Results: RBC lysis yielded higher percentage of PBMC (p = 0.0242) and higher numbers of PBMC/ml (p = 0.0039) than Ficoll. Absolute numbers of CD34 + CD133 + VEGFR2 + and CD146 + CD34 + VEGFR2 + were higher (p = 0.0117 for both), when isolated by RBC lysis than by Ficoll, when no difference in other subsets was found. Cryopreservation at -160°C and -80°C and short-term preservation at room temperature decreased EPC-EC.Conclusions: Our data support use of fresh samples and isolation of PBMC from human blood by RBC lysis for enumeration of EPC and EC.